Analisis Perencanaan Investasi Jaringan Tenaga Listrik - Dwi Ajiatmo; Henny Dwijayani (Universitas Darul Ulum, 2020)
Electricity is able to make a positive change and contribution to people's lives and well-being. This study aims to assess the feasibility of investment in the construction of low voltage electricity networks. The method used with project evaluation analysis is based on financial analysis. The criteria used to analyze activities carried out for 10 years use payback period (PP) analysis, net present value (NPV), internal rate of return (IRR), and profitability index (IP). The results showed that the analysis of investment planning can be carried out with the consequence of the results obtained in the form of not so large returns. PP results show the investment value with the payback period method will Return in the 9th year, while the positive NPV value is still above zero while the IRR value shows the value of 11% below the social discount rate as well as the IP value showing the value of 0.90. The feasibility of investment in terms of economic-financial analysis by looking at per criteria shows that investment is still feasible to be carried out with minimal profit levels.